Coffee-Derived Exosome-Like Nanoparticles: Are They the Secret Heroes? - Kantarcıoğlu, Murat; Yıldırım, Gülşen; Akpınar Oktar, Pınar; Yanbakan, Serpil; Özer, Zeynep Büşra; Yurtsever Sarıca, Deniz; Taşdelen, Serpil; Bayrak, Emel; Akın Balı, Dilara Fatma; Öztürk, Seçkin; Akçalı, Kamil Can; Ezer, Üstün; et al. (Turkish Journal of Gastroenterology, 2022)
Background: Regular coffee consumption has beneficial and preventative effects on liver and chronic neurodegenerative diseases. However, the studies performed with the ingredients found in coffee beverages have not clarified the responsible mechanisms. Exosomes are small, membrane-coated cargo packages secreted by prokaryote and eukaryote cells. Exosomes regulate intercellular communication and affect cellular metabolic activities even among different species. In this study, we aimed to isolate and characterize the edible plant-derived exosome-like nanoparticles from roasted hot coffee beverages, hypothesizing that the edible plant-derived exosome-like nanoparticles were responsible for the beneficial effects of coffee.Methods: Size exclusion chromatography and commercial kits were used for the isolation process. Efficient coffee edible plant-derived exosome-like nanoparticle fractions were determined by an ultraviolet-visible spectrophotometer. Harvested coffee edible plant-derived exosome-like nanoparticles were characterized by transmission electron microscopy. The quantification procedure was performed using a commercial kit. Coffee edible plant-derived exosome-like nanoparticles’ proliferative effects on human hepatic stellate cells and human hepatocellular carcinoma cells were studied using an MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay. Whole-exosome RNA sequencing was performed.Results: Transmission electron microscopy scanning analysis indicated round-shaped nanoparticles with sizes ranging from 40 to 100 nm. Both size exclusion chromatography and kit-isolated edible plant-derived exosome-like nanoparticle samples showed maximum absorbance at 227.5 nm in ultraviolet-visible spectrophotometer analysis. Regarding the quantitation results, kit isolation was more efficient than the size exclusion chromatography method when the harvested particle numbers were compared. An important MTT assay finding confirmed the observed beneficial effects of coffee beverages: coffee edible plant-derived exosome-like nanoparticles significantly suppressed hepatocellular carcinoma cell proliferation. As a result of sequencing, we identified 15 mature miRNAs. A MapReduce-based MicroRNA Target Prediction Method (The DIANA tools’ MR-microT algorithm) highlighted 2 genes specifically associated with the miRNAs that we obtained: KMT2C and ZNF773.Conclusion: For the first time in the literature, coffee edible plant-derived exosome-like nanoparticles were identified. These nanoparticles may have therapeutic effects on chronic liver diseases. Experimental studies, therefore, should be performed on disease models to demonstrate their efficacy.Cite this article as: Kantarcıoğlu M, Yıldırım G, Akpınar Oktar P, et al. Coffee-derived exosome-like nanoparticles: Are they the secret heroes? Turk J Gastroenterol. 2023;34(2):161-169.